The Correlation between Students’ Vocabulary Mastery and Their Reading Ability at Tenth Grade of SMAN 5 Kabupaten Tangerang - Muhammad Abdul Habil; Agus Mulyana; Hery Nuraini (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2023)
The purpose of this study was to determine the relationship between students' vocabulary mastery (X) and their reading ability (Y) in the tenth grade of SMAN 5 Kabupaten Tangerang in the academic year 2019/2020. There were 80 students from 403 students of population taken as the sample of this study who were determined using random sampling techniques. The data collected was analyzed using Pearson Product Moment Correlation and the instrument used was a student's vocabulary mastery test and a student's reading ability test. In addition, research findings indicate that there is a high correlation between students' vocabulary mastery and their reading ability. It is assumed that the alternative hypothesis (Ha) in this study was accepted and the null hypothesis (Ho) is rejected. There was correlation between students' vocabulary mastery and reading ability is accepted. In conclusion, the results of the hypothesis test between students' vocabulary mastery and reading ability in tenth grade at SMAN 5 Kabupaten Tangerang shows a positive correlation. There is a high correlation between students' vocabulary mastery and their reading ability at the SMAN 5 Kabupaten Tangerang with r-coef = 0.707. However, students must improve their learning, use their time perfectly, and have good mastery in memorizing vocabulary. In reading skills, students are strongly advised to always read books. So students are familiar with the support of English conversation.